The study of ground motion amplification based on an SMASS array site - Li, Ping; Zhou, Kai (Frontiers in Earth Science, 2022)
There is a consensus in earthquake engineering that different soil structures have significant effects on ground motion. Three main methods can be used to study this issue: theoretical analysis, numerical simulation, and earthquake records analysis. Notably, the combined analysis of strong-motion records and station site information appears to be the most effective and reliable approach. In this study, we used site information from the Seismic Monitoring Array of Site and Structure SMASS) of the Institute of Disaster Prevention and a record of the earthquake that occurred in Guye, China: a point on the bedrock was considered as reference for studying the amplification effect of the soil structure on ground motion through traditional spectral ratio analysis. Our main conclusions are the following. (1) The SMASS array data indicated that the shallow soil had an amplifying effect on ground motion: the frequency bands amplifying the horizontal ground motion were mainly those between 3.4–6.8, 11.3–13, and 15–20.8 Hz, while the frequency bands amplifying the vertical ground vibration were mainly those between 5–9.9, 13.5–15.9, and 18.5–21.9 Hz. (2) The SMASS array data indicated that the influence of the deep soil on the horizontal ground motion frequency component was more significant than that of vertical ground motion. (3) Overall, the SMASS array site amplified the effects of both the high (3.4–20.8 Hz) and low (0.4–2.2 Hz) frequency components of ground motion with the depth decreases of buried depth; notably, the amplification effect of the high-frequency components grew much faster than that of the low-frequency components. (4) The groundwater table had an amplification effect on the vertical ground motion; therefore, its influence is also important to consider.